Can chemical and molecular biomarkers help discriminate between industrial, rural and urban environments? - Garcia Alcega, Sonia; Nasir, Zaheer A.; Ferguson, Robert M. W.; Noël, Cyril; Cravo-Laureau, Cristiana; Whitby, Corinne; Dumbrell, Alex J.; Colbeck, Ian; Tyrrel, Sean; Coulon, Frederic (Elsevier, 2018)
Air samples from four contrasting outdoor environments including a park, an arable farm, a waste water treatment plant and a composting facility were analysed during the summer and winter months. The aim of the research was to study the feasibility of differentiating microbial communities from urban, rural and industrial areas between seasons with chemical and molecular markers such as microbial volatile organic compounds (MVOCs) and phospholipid fatty acids (PLFAs). Air samples (3 l) were collected every 2 h for a total of 6 h in order to assess the temporal variations of MVOCs and PLFAs along the day. MVOCs and VOCs concentrations varied over the day, especially in the composting facility which was the site where more human activities were carried out. At this site, total VOC concentration varied between 80 and 170 μg m−3 in summer and 20–250 μg m−3 in winter. The composition of MVOCs varied between sites due to the different biological substrates including crops, waste water, green waste or grass. MVOCs composition also differed between seasons as in summer they are more likely to get modified by oxidation processes in the atmosphere and in winter by reduction processes. The composition of microbial communities identified by the analysis of PLFAs also varied among the different locations and between seasons. The location with higher concentrations of PLFAs in summer was the farm (7297 ng m−3) and in winter the park (11,724 ng m−3). A specific set of MVOCs and PLFAs that most represent each one of the locations was identified by principal component analyses (PCA) and canonical analyses. Further to this, concentrations of both total VOCs and PLFAs were at least three times higher in winter than in summer. The difference in concentrations between summer and winter suggest that seasonal variations should be considered when assessing the risk of exposure to these compounds.
Keywords: MVOCs; PLFAs; Bioaerosols; Thermal desorption; Chemometrics; Outdoor environments; Air quality